Wave-shaped interlocking interface reinforced aluminum alloy laminated material and forming method thereof
By introducing ceramic hard particles into the intermediate layer of the laminated aluminum alloy material and forming a "wave-like" interlocking interface through extrusion deformation, the peeling or layering problems caused by stress concentration of traditional laminated aluminum alloy materials are solved, and the interface bonding strength and impact resistance are significantly improved.
Patent Information
- Application Number
- CN202410672056.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-28
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-05-28
AI Technical Summary
Traditional laminated aluminum alloy materials are prone to stress concentration during use, resulting in peeling or layering, affecting the performance stability of the material.
By introducing ceramic hard particles into the intermediate layer and extruding them with the soft pure aluminum layer by rolling deformation, forming a "wavy" interlocking interface, thereby improving the interface bonding strength.
Effectively hinder crack propagation, change the crack propagation direction, and improve the interface bonding strength and impact resistance of aluminum alloy laminated materials.
Smart Images

Figure CN119748987A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite material preparation, and in particular relates to a "wavy" interlocking interface strengthened aluminum alloy laminate material and a forming method thereof. Background Art
[0002] With the development of industry and technology, the requirements for material performance and application are constantly increasing. Traditional single metal materials can no longer meet the needs of complex engineering. Laminated aluminum alloys have the advantages of low density, high specific strength, and good welding performance, and are widely used in new energy vehicles, aerospace, high-speed rail, tank armor and other fields. During the preparation process of laminated aluminum alloys, uneven stress distribution will occur between different layers, causing stress concentration, which will lead to peeling or stratification of the material during use, affecting the performance stability of the laminated aluminum alloy and causing component failure. Therefore, it is very urgent to develop laminated aluminum alloys with high interface bonding.
[0003] In order to improve the interfacial bonding strength of laminated armor, existing research mainly improves the interfacial strength of laminated materials through surface treatment, rolling process optimization, and diffusion annealing. The research results show that removing surface oxide film and oil, appropriately increasing rolling temperature and rolling deformation, reducing rolling speed, and suitable diffusion annealing temperature are all conducive to improving the bonding strength of laminated aluminum alloys. However, the above methods mainly improve the bonding strength of laminated aluminum alloys from the material perspective through metallurgical bonding, and the room for improvement is limited. Therefore, in order to solve the interface bonding problem, designing a "wavy" interlocking interface to strengthen the interface bonding strength of aluminum alloy laminated materials has become an urgent need in this field. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for strengthening the interface bonding of aluminum alloy laminated materials by a "wavy" interlocking interface; the present invention utilizes the extrusion effect of ceramic hard particles on the interface of the soft pure aluminum layer to obtain a "wavy" interlocking interface to achieve high interface bonding. The formation of the "wavy" interlocking interface can effectively hinder the propagation path of the crack, thereby changing the direction of crack propagation to improve the interface bonding strength of the aluminum alloy laminated material.
[0005] The present invention discloses a method for strengthening the interface bonding of aluminum alloy laminated materials by a "wavy" interlocking interface. The "wavy" interlocking interface is that when the ceramic hard particles evenly distributed in the middle layer are subjected to rolling deformation force, the ceramic particles near the interface are subjected to external force to squeeze the soft pure Al layer, and the pure Al layer at the squeezed position is concave toward the aluminum alloy layer, and the positions near the two ends of the ceramic particles are convex toward the mixed powder middle layer, thereby promoting the formation of the "wavy" interlocking interface. The ceramic particles are selected from SiC particles, and the particle size is greater than or equal to 20 microns and less than or equal to 200 microns; the thickness of the pure aluminum layer is less than or equal to 100 microns.
[0006] The present invention discloses a "wavy" interlocking interface strengthened aluminum alloy laminated material; it comprises at least two substrates and an intermediate layer distributed between adjacent substrates, the intermediate layer contains hard particles and a soft layer, the hardness of the soft layer is less than that of the substrate, the "wavy" interlocking interface is formed by mutual extrusion and deformation of the ceramic hard particles and the soft layer in the intermediate layer, and the "wavy" interlocking interface is located between the extruded substrate and the intermediate layer. The substrate is an aluminum alloy; the hardness of the hard particles is greater than or equal to 500HV.
[0007] The interface has a "wavy" microscopic interface morphology, which increases the mechanical bite effect of the laminate interface, thereby improving the interface bonding strength of the aluminum alloy laminate material.
[0008] Preferably, the material of any one of the substrates is selected from 2024Al, 6061Al, 7075Al, 7A52Al, and 7A62Al, preferably 2024Al.
[0009] The hard particles are selected from at least one of SiC powder, glass powder and diamond powder, and are preferably SiC powder.
[0010] The material of the soft layer is one of pure aluminum, aluminum alloy, zinc alloy and magnesium alloy.
[0011] The present invention discloses a method for preparing a "wavy" interlocking interface strengthened aluminum alloy laminate material, comprising the following steps: firstly, a soft layer is arranged on the surface of a substrate, and ceramic powder and metal powder are evenly mixed by ball milling; the mixed powder is placed between two layers of substrates and compacted to form a fixed "sandwich" combination structure of substrate-soft layer-mixed powder layer-soft layer-substrate, the combined laminate material is solution treated and then immediately hot rolled, and after rolling, an aging treatment is performed to obtain the "wavy" interlocking interface strengthened aluminum alloy laminate material.
[0012] When applied in industry, a layer of pure aluminum is first electroplated on the surface of the aluminum alloy plate, and ceramic powder and metal powder are ball-milled and mixed. The mixed powder is placed between two layers of aluminum alloy plates and compacted to form a fixed "sandwich" combination structure of aluminum alloy-mixed powder layer-aluminum alloy. The combined laminated material is immediately hot-rolled after solid solution treatment, and then aging treatment is performed after rolling to obtain an aluminum alloy laminated material with a "wavy" interlocking interface reinforcement.
[0013] The thickness of a soft layer is 10-100 microns, preferably 40-60 microns. If the soft layer is too thin, the "wavy" interlocking interface will be discontinuous, and if the soft layer is too thick, the SiC hard particles will not be able to completely squeeze the soft layer, affecting the formation of the "wavy" interlocking interface.
[0014] The ceramic powder is selected from one of SiC powder, glass powder and diamond powder, and is preferably SiC powder.
[0015] Metal particles are selected from ZnAl 20 、ZnAl 15 , and ZnAl3, preferably pure ZnAl3 powder.
[0016] The particle size of the ceramic powder is 20-200 microns, preferably 50-150 microns, and more preferably 100 microns.
[0017] The particle size of the metal powder is 20-200 microns, preferably 50-150 microns, and more preferably 100 microns.
[0018] The volume ratio of ceramic powder to metal powder in the mixed powder is ceramic powder: metal powder = 1: 1-3, preferably ceramic powder: metal powder = 1: 2-3. The content of the selected ceramic powder is from low to high. When the volume ratio of ceramic powder to metal powder is greater than 1: 1, an effective interface bonding cannot be formed, and the laminated material will crack during rolling.
[0019] The thickness of a single mixed powder layer is approximately the same as the thickness of a single aluminum alloy plate, which is 1-6 mm, preferably 2.5-3.5 mm.
[0020] The thickness of the soft layer should be smaller than the particle size of the ceramic powder in order to allow the ceramic particles to squeeze the entire soft layer and increase the probability of forming a "wavy" interlocking interface.
[0021] During the solution treatment of the present invention, the temperature is controlled to be 515-525° C. and the treatment time is 55-65 minutes.
[0022] The present invention performs hot rolling after solution treatment, the rolling deformation is 30-60%, preferably 48-52%, and the strain rate is 2.2-9.6s -1 , preferably 4.9 to 4.95 s -1 Finally, an aging treatment is performed at 170 to 190° C. for 12 to 48 hours, preferably 20 to 28 hours.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The present invention designs an aluminum alloy laminate material with a "wavy" interlocking interface through hot rolling treatment. For the first time, the "wavy" interlocking interface of the laminate structure is realized by introducing hard particles into the soft layer and the middle layer through interface design, thereby suppressing the defect of easy cracking of the interface of the composite plate and obtaining better interface bonding strength. The hard particles and the "wavy" interlocking interface change the traditional straight fracture mode into a curved fracture along the particles, increasing the path of crack propagation. The introduction of hard particles not only enhances the bonding strength of the laminate interface by changing the fracture mode, but also improves the impact strength.
[0025] In summary, the process of the present invention is relatively simple, has no environmental pollution similar to explosive welding, has low cost, and is easy to control the interface morphology. The prepared laminated composite material has a unique structure and greatly improves the bonding strength of the material. It is of great significance to the development of my country's aerospace and national defense military industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The morphology of the "wavy" interlocking interface with different SiC contents in Comparative Example 1 and Example 1 of the present invention;
[0027] Figure 2 The interface bonding strength of aluminum alloy laminated materials with different SiC contents in Comparative Example 1 and Example 1 of the present invention;
[0028] Figure 3 The shear fracture positions of the aluminum alloy laminated materials with different SiC contents in Comparative Example 1 and Example 1 of the present invention;
[0029] Figure 4 The impact strength of aluminum alloy laminates with different SiC contents in Comparative Example 1 and Example 1 of the present invention;
[0030] Figure 1 In the figure, a is the interface morphology of sample No. 1, b is the interface morphology of sample No. 2, c is the interface morphology of sample No. 3, and d is the interface morphology of sample No. 4; Figure 1 It can be seen that there are obvious differences in the morphology of the "wavy" interlocking interface with different SiC contents.
[0031] from Figure 2 It can be seen that the interface bonding strength of aluminum alloy laminates with different SiC contents.
[0032] from Figure 3 It can be seen that the interface morphology of sample No. 1 without SiC particles is straight, and the shear fracture position is close to the interface. The shear fracture position of sample No. 4, which forms a "wavy" interlocking interface, breaks along the holes formed by the aggregation of SiC particles, and the interface bonding strength of sample No. 4 is higher than that of sample No. 1. This proves that the "wavy" interlocking interface has a higher interface bonding strength than the straight interface.
[0033] from Figure 4 It can be seen that with the increase of SiC content, not only a "wavy" interlocking interface is formed, but also the impact resistance of the laminated composite material is improved. DETAILED DESCRIPTION
[0034] In order to further deepen the understanding of the present invention, the present invention is described in detail below in conjunction with the embodiments. It must be pointed out that the protection scope of the present invention is not limited by the following embodiments.
[0035] Comparative Example 1
[0036] (1) Preparing a number of aluminum alloy plates and aluminum alloy mold frames using laser cutting technology;
[0037] (2) The surface of a 2 mm thick 2024 aluminum alloy plate was polished to be smooth, and after removing the oil and oxide layer on the surface, a pure aluminum layer (thickness of about 50 microns) was plated on the surface of the plate by electroplating. An aluminum-plated aluminum alloy plate was placed in the frame of an aluminum alloy mold, and pure ZnAl3 powder was evenly spread on the aluminum alloy plate (the powder layer thickness was about 2 mm), and another aluminum-plated aluminum alloy plate was placed on the powder layer. A laminated sample of aluminum alloy plate-ZnAl3 powder layer-aluminum alloy plate was formed.
[0038] (3) The laminated sample was solution treated at 520°C for 1 h and then hot rolled with a rolling deformation of 50% and a strain rate of 4.92s -1 Finally, an aging treatment was performed at 180°C for 24 hours to obtain Comparative Example No. 1 sample.
[0039] Example 1
[0040] (1) Preparing a number of aluminum alloy plates and aluminum alloy mold frames using laser cutting technology;
[0041] (2) Powder mixing: 100 μm ZnAl3 alloy powder (zinc content: 97%, aluminum content: 3%) and 100 μm SiC powder were placed in a ball mill at a volume ratio of 3:1, 2:1, and 1:1, and ball milled for 4 h at a ball mill speed of 300 r / min.
[0042] (3) Combination: The surface of a 2 mm 2024Al alloy plate was polished to be smooth, and after removing the oil and oxide layer on the surface, a pure aluminum layer (thickness of about 50 microns) was plated on the surface of the plate by electroplating. A piece of aluminum-plated aluminum alloy plate was placed in the frame of an aluminum alloy mold, and SiC-ZnAl3 mixed powders of different volume ratios were evenly spread in the middle of the aluminum alloy plate (the thickness of the powder layer was about 2 mm), and then another piece of aluminum-plated aluminum alloy plate was placed on the powder layer, and the operation was repeated. According to the combination of 1 layer of metal plate, 1 layer of mixed powder and 1 layer of metal plate, it was repeated 3 times to obtain sample No. 2, sample No. 3, and sample No. 4, wherein the mixed powder layer in sample No. 2 was composed of SiC powder and ZnAl3 alloy powder in a volume ratio of 1:3. The mixed powder layer in sample No. 3 was composed of SiC powder and ZnAl3 alloy powder in a volume ratio of 1:2, and the mixed high-strength layer in sample No. 4 was composed of SiC powder and ZnAl3 alloy powder in a volume ratio of 1:1. Finally, the gap between the aluminum alloy forming mold and the aluminum alloy plate is sealed with 1000°C high-temperature glue, and the laminated composite material is wrapped with a layer of aluminum foil to isolate oxygen.
[0043] (3) After solution treatment at 520 °C for 1 h, hot rolling was performed with a rolling deformation of 50% and a strain rate of 4.92 s -1 Finally, an aging treatment was performed at 180°C for 24 hours to finally obtain samples No. 2, 3, and 4 of Examples.
[0044] The improvement of interface bonding strength is as follows: With the increase of SiC content, the number of SiC particles near the interface increases, which increases the probability of forming a "wavy" interlocking interface. Figure 1 As shown. Figure 2 It can be seen that when the volume ratio of ZnAl3 powder to SiC powder is 3:1, sample No. 2 has the maximum interface bonding strength of 52.57MPa, which is 44.46% higher than sample No. 1 without SiC powder. With the increase of SiC powder content, the interface bonding strength decreases mainly because the excessive SiC particles form holes and cracks, and the cracks mainly extend along the holes and cracks. The addition of SiC particles forms a "wavy" interlocking interface, which changes the location of shear fracture, such as the attached Figure 3 As shown. The interface morphology of sample No. 1 without SiC particles added is straight, and the shear fracture position is close to the interface. The shear fracture position of sample No. 4, which forms a "wavy" interlocking interface, breaks along the holes formed by the aggregation of SiC particles. The interface bonding strength of sample No. 4 is higher than that of sample No. 1, which further proves that the formation of the "wavy" interlocking interface can effectively improve the interface bonding strength of aluminum alloy laminates. In addition, the introduction of SiC hard particles increases the impact strength of aluminum alloy laminates from 511MPa to 618MPa, as shown in the attached figure. Figure 4 shown.
Claims
1. A "wavy" interlocking interface strengthened aluminum alloy laminated material; characterized in that: The invention comprises at least two substrates and an intermediate layer distributed between adjacent substrates, wherein the intermediate layer contains hard particles and a soft layer, wherein the hardness of the soft layer is less than that of the substrate, and the "wavy" interlocking interface is formed by mutual extrusion and deformation of the ceramic hard particles and the soft layer in the intermediate layer, and the "wavy" interlocking interface is located between the extruded substrate and the intermediate layer. The substrate is an aluminum alloy; and the hardness of the hard particles is greater than or equal to 500 HV.
2. A "wavy" interlocking interface strengthened aluminum alloy laminate material according to claim 1; characterized in that: The material of any one of the substrates is selected from one of 2024Al, 6061Al, 7075Al, 7A52Al, and 7A62Al; The hard particles are selected from at least one of SiC powder, glass powder and diamond powder, preferably SiC powder; The material of the soft layer is one of pure aluminum, aluminum alloy, zinc alloy and magnesium alloy.
3. A method for preparing a "wavy" interlocking interface strengthened aluminum alloy laminated material, characterized in that: The following steps are involved: First, a soft layer is set on the surface of the substrate, and the ceramic powder and the metal powder are ball-milled and mixed evenly; the mixed powder is placed between two layers of substrates and compacted to form a fixed "sandwich" combination structure of substrate-soft layer-mixed powder layer-soft layer-substrate, and the combined laminated material is immediately hot-rolled after solution treatment, and then aged after rolling to obtain an aluminum alloy laminated material with a "wavy" interlocking interface reinforcement.
4. The method for preparing a "wavy" interlocking interface strengthened aluminum alloy laminated material according to claim 3, characterized in that: The thickness of the soft layer is 10-100 microns, preferably 40-60 microns.
5. The method for preparing a "wavy" interlocking interface strengthened aluminum alloy laminated material according to claim 3, characterized in that: The ceramic powder is selected from one of SiC powder, glass powder and diamond powder, preferably SiC powder; the metal particles are selected from ZnAl 20 、ZnAl 15 , and ZnAl3, preferably pure ZnAl3 powder.
6. The method for preparing a "wavy" interlocking interface strengthened aluminum alloy laminated material according to claim 3, characterized in that: The particle size of the ceramic powder is 20-200 microns, preferably 50-150 microns, and more preferably 100 microns. The particle size of the metal powder is 20-200 microns, preferably 50-150 microns, and more preferably 100 microns.
7. The method for preparing a "wavy" interlocking interface strengthened aluminum alloy laminated material according to claim 3, characterized in that: The volume ratio of the ceramic powder to the metal powder in the mixed powder is ceramic powder:metal powder=1:1-3, preferably ceramic powder:metal powder=1:2-3.
8. The method for preparing a "wavy" interlocking interface strengthened aluminum alloy laminated material according to claim 3, characterized in that: The thickness of a single mixed powder layer is approximately the same as the thickness of a single aluminum alloy plate, which is 1-6 mm, preferably 2.5-3.5 mm.
9. The method for preparing a "wavy" interlocking interface strengthened aluminum alloy laminated material according to claim 3, characterized in that: During solution treatment, the temperature is controlled at 515-525°C and the treatment time is 55-65 minutes. After solution treatment, hot rolling is performed, with a rolling deformation of 30-60% and a strain rate of 2.2-9.6s -1 Finally, an aging treatment is performed at 170-190°C for 12-48 hours.
Citation Information
Patent Citations
Degradable zinc-base metal ceramic with enhanced mesh-like particles and preparation method thereof
CN110423911A
Layered aluminum alloy / aluminum-based composite board and preparation method thereof
CN113385534A
High-performance trumpet shell bionic structure aluminum-based composite armor and forming method thereof
CN116275053A
Metal matrix composite material
US20090220814A1